The impact of chronic orofacial pain on health-related quality of life - Heli Forssell; Kirsi Sipilä; Tuija Teerijoki-Oksa; Pekka Vartiainen; Hannu Kautiainen; Harri Sintonen; Eija Kalso (De Gruyter, 2022)
Background and aims
Health-related quality of life (HRQoL) assessments have been widely used in pain medicine as they are able to reflect the subjective and multidimensional nature of chronic pain. Studies have shown a consistent impairment in HRQoL in different chronic pain conditions. However, it is not known whether HRQoL is impaired in chronic orofacial pain (OFP). The generic 15D HRQoL instrument has been shown to fare as well as or better than other generic HRQoL instruments in the study of chronic pain. The aim was to investigate HRQoL in patients with chronic OFP using the generic 15D HRQoL instrument. The validity of the instrument was tested by studying the association of the 15D data with pain interference.
Methods
One hundred fifty-one patients (mean age 50 years, SD 15 years, 119 females) were recruited from three tertiary facial pain clinics. HRQoL data of the participants were contrasted with that of an age- and gender- standardized sample of general population by comparing the mean 15D scores and profiles. The data for the general population came from the National Health 2011 Survey representing Finnish population aged 18 years and older. Pain interference was assessed using Brief Pain Inventory. Based on pain interference distribution the participants were divided into tertiles. Statistical comparison between patient and population HRQoL values were performed using Monte-Carlo-type simulations. Statistical significance for the hypothesis of linearity was evaluated by using generalized linear models.
Results
The mean 15D score of OFP patients (0.824, SD 0.113) was statistically significantly lower than that of the age- and gender-standardized general population (0.929, SD 0.019) (p < 0.001). The difference between the patients and the general population was also clinically important, i.e. over the minimum clinically important difference in the 15D score. All mean 15D dimension values were significantly lower compared with the general population values (p < 0.001 for all dimensions). The largest differences were seen in the dimensions of discomfort and symptoms (0.418, SD 0.222 vs. 0.816, SD 0.027), sleeping (0.693, SD 0.258 vs. 0.838, SD 0.029), and vitality (0.702, SD 0.221 vs. 0.884 SD 0.026). There was a statistically significant linear decrease in the 15D dimension values (p < 0.001) with increasing pain interference. The greatest differences were found on the dimensions of discomfort and symptoms, sleeping and vitality.
Conclusions
HRQoL is significantly impaired in patients with chronic OFP. A decrease in the 15D dimension values with increasing pain interference indicated convergent validity between 15D and pain interference.
Implications
The findings suggest that 15D is an appropriate instrument for use in the assessment of HRQoL in OFP patients. By showing the usefulness of the 15D, the present study may encourage further use of generic HRQoL assessments in the study of chronic OFP, and contribute e.g. to the implementation of HRQoL as one of the core outcome measures in future treatment studies on chronic OFP.
This article offers supplementary material which is provided at the end of the article.